Evaluasi Penurunan Tekanan Darah Pada Pasien Hipertensi Setelah Dilakukan Bekam - Suciana, Fitri; Pratiwi, Adelia Wahyu (Yayasan Jompa Research and Development, 2025)
Background: Cupping is a therapeutic method performed by suctioning the skin in certain areas to remove toxins and oxidants from the body through thin incisions that hit the capillaries in the epidermis layer. In Islam, cupping is known as a form of health therapy and is also referred to as Al-Hijamah, which comes from the word Al-Haj which means “to suck.” One of the benefits of cupping is that it helps to reduce pressure. One of the benefits of cupping is that it helps lower blood pressure by removing plaque that triggers hypertension through blood that is removed from the body.Research Objective: This study aims to assess the impact of wet cupping therapy on lowering blood pressure in hypertensive patients.Research Methods : This study used a quasi-experiment design with the Pre-Post Test with Control Group Design method. Normality tests were carried out using the Shapiro-Wilk method, while differences between variables were tested using Independent T-Test and Paired T-Test to see if there were changes after the intervention.The results showed the normality test results of all data were normally distributed. Analysis using Paired T-Test showed significant changes in both groups after undergoing wet cupping therapy and routine drug consumption, with a P-value <0.05. Meanwhile, the Independent T-Test results also showed a significant difference between the two groups with a P-value <0.05.Conclusion There is a decrease in the average systolic and diastolic pressure in hypertensive patients after cupping.